Retrospective comparison of split-thickness skin graft versus local full-thickness skin graft coverage of radial forearm free flap donor site. Issue 8 (August 2022) - Vahldieck, Michael; Zyba, Vitalij; Hartwig, Stefan; Paßmann, Benedikt; Scheer, Martin
Abstract: The study aimed at comparing outcomes between split-thickness skin graft (STSG) and local ipsilateral full-thickness skin graft (FTSG) after radial forearm free flap defect closure. A comprehensive study protocol for objective and subjective assessment was established for this retrospective, single-center study. Clinical examinations were carried out, encompassing measuring wrist and finger range of movement and grip strength, testing skin sensitivity, and evaluating aesthetics using the Patient and Observer Scar Assessment Scale (POSAS). In addition, medical history, and questionnaire, including Cold Intolerance Severity Score (CISS) and 18 items, were used to assess satisfaction, functional limitations, and complaints. 44 patients were examined, and 40 patients included, who had received STSG (group 1; n = 19) respectively local FTSG from the ipsilateral forearm (group 2; n = 21) at least three months previously. Significantly lower values for parameters pigmentation, relief (p = 0.015), overall impression (p = 0.044), as well as mean POSAS observer scale total score (p = 0.046) and no complaints wearing a wristwatch (p = 0.012) were shown in group 2 (FTSG). Within the limitations of the study, it seems that FTSG harvested from the forearm should be preferred over STSG to cover RFFF donor site whenever appropriate, because of beneficial outcomes, while providing single intervention closure and avoiding secondary donor site.